KINERJA BAGIAN PROTOKOLER DI SEKRETARIAT DAERAH KABUPATEN PASANGKAYU - Sadahi Wahid; Abdul Rivai; Nawawi Natsir (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The phenomenon that occurred in the Protocol Section at the Regional Secretariat of Pasangkayu Regency, has been going well but there are still several things that are not optimal, namely delays in work attendance so that in implementing performance in the areas of coordination, coaching, policy formulation, program planning, evaluation and reporting on the implementation of Public Relations and Protocol activities related to reporting, documentation and protocols. It can be seen that performance is hampered or hampered. The aim of this research is to determine the performance of the Protocol Section at the Pasangkayu Regency Regional Secretariat, which is studied based on the performance theory model according to Anwar Prabu Mangkunegara (2019: 67), namely: Work quantity, work quality, work discipline, work initiative, responsibility. The type of research used is qualitative descriptive with purposive sampling of informants. The results of research on the performance of the protocol section at the Pasangkayu Regency Regional Secretariat can be concluded as follows: The results of the research show that performance in terms of quantity and quality has gone well, this shows that employees are capable of achieving performance. Performance in terms of discipline means that there is implementation of work discipline starting from the level of electronic attendance, morning roll call and use of official uniforms, there are still employees who commit violations of work discipline, especially during working hours where they are not optimally carrying out their obligations with indicators of complying with working hours provisions, p. This can be seen from the fact that there are still employees who do not comply with working hours provisions, such as employees often not coming to work, entering and leaving the agency not in accordance with regulations and often entering the office late. Performance in terms of initiative means that in carrying out their duties, employees always help each other with colleagues in completing tasks without any orders from superiors. Performance in terms of responsibility means that employees are able to complete tasks well in accordance with the specified time, however, in terms of discipline, employee performance is still not optimal. The obstacles to the performance of the Protocol Section at the Regional Secretariat of Pasangkayu Regency are the lack of employees so that the work carried out by employees is overwhelmed and they have difficulty carrying out superiors' orders, in addition to the reduction in the number of employees and the lack of optimal support for employee work in the form of facilities and infrastructure, namely an internet network that is too slow resulting in work employees are hindered in carrying out their duties so that employees' work is neglected.